Effect of Composition on the Physical Properties at Nanoscale of PZT Thin Films - Lima, E. C.; Araujo, E. B. [UNESP]; Bdikin, I. K.; Kholkin, A. L. (Taylor & Francis Ltd, 2014)
PbZr1-xTixO3 (PZT) thin films (x = 0.46, 0.47, 0.48, 0.49, and 0.50) were deposited on Pt/TiO2/SiO2/Si substrates using a polymeric chemical method to study the effects of the composition on the macroscopic electrical and local piezoelectric properties. Both measurements demonstrate the existence of a self-polarization effect in all studied PZT films. The measurements were discussed in terms of the contribution of the Schottky barriers to the self-polarization effect. It is shown that both Schottky barrier effect and mechanical coupling near the film-substrate interface are not the dominant mechanisms responsible for the observed phenomena.
Keywords: Piezoelectric; piezoresponse; self-polarization